2019
DOI: 10.1055/a-0838-6062
|View full text |Cite
|
Sign up to set email alerts
|

No Connection between Long-Term Lithium Treatment and Antithyroid Antibodies

Abstract: Introduction The studies on the effect of lithium treatment on antithyroid antibodies showed either a higher concentration of these antibodies in patients receiving lithium compared to those lithium-naive or no difference between these groups. In lithium-treated bipolar patients, some researchers pointed to an association between antithyroid antibodies and other features of thyroid dysfunction such as hypothyroidism and decrease of glomerular filtration rate. Methods We compared antithyroid antibodies in 98 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
2
5
0
1
Order By: Relevance
“…29 No connection was found between long-term lithium treatment and antithyroid antibodies. 30 We also observed similar indexes of thyroid function in bipolar patients who had used lithium for 10-20 years and in those who had used it for 20 years or more. 31 The most common renal adverse effect of lithium is decreased renal concentrating capacity, which can appear after a few weeks of lithium use.…”
Section: Adverse Effects Of Long-term Lithium Treatmentsupporting
confidence: 75%
See 1 more Smart Citation
“…29 No connection was found between long-term lithium treatment and antithyroid antibodies. 30 We also observed similar indexes of thyroid function in bipolar patients who had used lithium for 10-20 years and in those who had used it for 20 years or more. 31 The most common renal adverse effect of lithium is decreased renal concentrating capacity, which can appear after a few weeks of lithium use.…”
Section: Adverse Effects Of Long-term Lithium Treatmentsupporting
confidence: 75%
“… 29 No connection was found between long-term lithium treatment and antithyroid antibodies. 30 We also observed similar indexes of thyroid function in bipolar patients who had used lithium for 10-20 years and in those who had used it for 20 years or more. 31 …”
Section: Adverse Effects Of Long-term Lithium Treatmentsupporting
confidence: 75%
“…Furthermore, in both lithium and nonlithium groups, there were other mood stabilizers such as valproate, carbamazepine, or quetiapine that make frequent modalities of BD prophylaxis (Musetti et al, ) and could exert an effect on thyroid function. We also did not correlate our results with those of antithyroid antibodies as it has been described elsewhere (Kraszewska et al, ). Another limitation can be a lack of a healthy comparison group.…”
Section: Discussionmentioning
confidence: 67%
“…The second aim of the study was to investigate a relationship between lithium effect on hormonal function and the structure of the thyroid gland. The assessment of antithyroid antibodies in these groups of patients has been a subject of a separate paper (Kraszewska, Ziemnicka, Sowinski, Ferensztajn‐Rochowiak, & Rybakowski, ).…”
Section: Introductionmentioning
confidence: 99%
“…The thyroid structure showed a higher thyroid volume and a higher incidence of goiter (Kraszewska et al 2019a). No significant differences were found between the groups of antithyroid antibodies (Kraszewska et al 2019b). A recent study also found that the effect on function and structure may be modified by adding other mood stabilisers and antidepressant drugs to lithium (Kraszewska et al 2019c).…”
Section: ( Introductionmentioning
confidence: 97%